Parental treatment styles and their relationship to psychological adjustment among fourth year primary students - Bakhta CHETTOUH (Social Sciences Journal, 1970)
This study aims to reveal the nature of the relationship between parental transaction methods(mother/father), and its relation with the psychological compatibility of students of forth yearprimary school, in addition to the recognition of the differences between the sample membersin both variables according to the sex and parents educational level within the DescriptiveCorrelative Approach. This study relies on a sample of (140) pupil of forth year primaryschool in Laghouat. 69 of them are males and 71 are females their ages are between (9 and11). We used two measures: parental Treatment methods (the mother/the father), (Anafiai,1992), and the Psychological compatibility (Chkir ,2003), we rely also on the Statisticalpackage of sociology , in extracting the arithmetic averages , the standards deviations , thelink transactions , examination(s) , and the analysis of mono – variance . The study concludedthat there is no linked relationship of the treatment methods and its dimensions, and the totaldegree of the psychological integration. The study concluded also that there are noيعهح انؼهٕو االظرًاػٙج انؼذد 27َٕ فًثش2017141differences between males and females in the degree of parental treatment methods (thefather/the mother), and in the psychological integration and its dimensions. It brought outthat there are no differences between the parental treatment methods with its dimensions, andthe psychological integration with educational level of parent. According to the results of thisstudy we raise alert to the ears of parents that it a must to practice positive treatment methodsdue its influence on the psychological integration. Also it is must to establish Guidance andguidance centers which guide both parents and their children to solve the problems correctlyand wisely. In addition to raising the awareness and interest toward the correct parentaltreatment methods through different media means, and its positives toward pupils integration.inside and outside the school